Translation Analysis on Dayak Cultural Terms From Dayak Ngaju to Indonesian and English - Lida Karyani; Mangatur Rudolf Nababan; Sri Marmanto (Langkawi: Journal of The Association for Arabic and English, 2020)
The research aimed to describe the translation techniques and translation qualities of Dayak cultural terms.  The data were obtained from tatum, an oral culture of Dayak that had been transcribed and rewritten in Dayak Ngaju, Indonesian and English in a book entitled The Ot Danum from Tumbang Miri until Tumbang Rungan. The research used descriptive qualitative method with content analysis. It attempted to explain the translation techniques and translation qualities of Dayak cultural terms that were translated from Dayak Ngaju to Indonesian and from Indonesian to English. The Dayak cultural terms analysed were related to organization, customs, belief, and kinship system of Dayak. The translation techniques of Dayak cultural terms from Dayak Ngaju to Indonesian were pure borrowing, naturalized borrowing, established equivalent, generalization, variant borrowing, description, and amplification, and the translation qualities were 2.80 of accuracy and 2.84 of acceptablity.  The Dayak cultural terms found in the target language (Indonesian translation) were decreased in number as the effect of the translation techniques used. The translation technique of Dayak cultural terms from Indonesian to English was pure borrowing, and the translation quality were 3 of accuracy and 2.75 of acceptability.